Actinomycetoma caused by Nocardia otitidiscaviarum: Report of a case in Taiwan with long-term follow-up - Min-Hui Chi; Rosaline Chung-Yee Hui; Chin-Fang Lu; Li-Cheng Yang; Shu-Ying Li (Wolters Kluwer Medknow Publications, 2013)
Actinomycetoma is a chronic granulomatous infection, with Nocardia species being one of the infecting pathogens. Infections caused by N. otitidiscaviarum are relatively rare compared with those caused by other Nocardia species. Conventional methods for the diagnosis of nocardiosis based on phenotypic characterization of the strains (e.g., morphology, histopathology) are relatively time consuming and nonspecific. Molecular techniques have become the better choice for prompt and accurate identification of Nocardia isolates. We report a case of actinomycetoma due to N. otitidiscaviarum characterized by 16S ribosomal RNA (16S rRNA) gene sequence analysis and the long-term follow-up.